Bankruptcy and Agency Costs: Their Significance to the Theory of Optimal Capital Structure - Haugen, Robert A.; Senbet, Lemma W. (Journal of Financial and Quantitative Analysis, 1988)
Robert A. Haugen, Lemma W. Senbet, Bankruptcy and Agency Costs: Their Significance to the Theory of Optimal Capital Structure, The Journal of Financial and Quantitative Analysis, Vol. 23, No. 1 (Mar., 1988), pp. 27-38